Fatores abióticos na fisiologia de sementes e madas de Luetzelburgia auriculata (Alemão) Ducke - Lopes, Maria de Fátima de Queiroz (2018)
The Caatinga Biome is unique to Brazil and constitutes one of the richest in biodiversity, despite the constant anthropic disturbances. On the other hand, it is necessary to recover the degraded areas, especially in places with an accelerated process of devastation. The objective of this work was to study the effects of abiotic factors on seed physiology and seedlings of Luetzelburgia auriculata (German) Ducke from two mass classes. For this, the seeds of Luetzelburgia auriculata were collected manually at the Poço da Pedra Farm, located in the city of Caridade-CE and sent to the Laboratory of Seed Analysis of the UFPB in Areia-PB. Prior to the installation of the experiment, each seed unit was individually weighed on an analytical scale (0.001 g) to divide the sample into two classes of light, (<0.35 g) and heavy (≥ 0.35 g) seeds. The water content (TA) and the weight of one thousand seeds (PMS) were first determined, after which the seed classes were submitted to saline and water stresses. As for the first one, the levels of 0,0 were used; 1.5; 3.0; 4.5 and 6.0 dS m-1 with germination (G%), first germination count (PCG), germination speed index (IVG), mean germination time (TMG), shoot length CPA), root length (CR), fresh shoot mass (MFPA), fresh root mass (MFR), fresh cotyledon mass (MFCot), shoot dry mass (MSPA), fresh root mass (MFR), and cotyledon dry mass (MSCot). For water stress, the potentials studied were: 0.0; -0.2; -0.4; -0.6; -0.8 and -1.0 MPa, evaluating, at this stage, the same variables listed above, except for CPA, MFPA, MSPA. Subsequently, in a protected environment, the seedlings produced were analyzed for gaseous exchange and their relationships with meteorological components. The variables studied were: Ambient temperature (TA) and relative humidity (UR), net photosynthesis rate (A), conductance stomatal (gs), internal carbon (Ci), transpiration (E), leaf temperature (TF), water use efficiency (A/E) and carboxylation efficiency (A/Ci). With increasing saline and water stresses, a harmful effect was observed in most of the morphological and physiological variables in both seed classes. Regarding the seedlings, high magnitude correlations were verified between the variables TA, UR, A, E, gs, E, Ci and A/E. The rate of liquid photosynthesis, transpiration and stomatal conductance decreases throughout the day, presenting minimum values at 16 hours. In general, heavy seeds (≥ 0.35 g) are more adapted to the water and saline stresses, so that the physiological quality of light seeds was affected by drought and salinity. The seed class does not influence the gas exchange of the seedlings, but these variables are influenced by the hours of the day and, therefore, are dependent on meteorological factors.